Dahlia spp. Dahlia: FPS169/FP169, 6/2007 - Gilman, Edward; Howe, Teresa (EDIS, 2007)
This document provides comprehensive information on the cultivation and care of dahlias. It covers the ideal soil conditions, planting times, and maintenance practices to ensure healthy growth and vibrant blooms. The text also details the various pests and diseases that can affect dahlias, along with methods for propagation and overwintering. Additionally, it highlights the plant’s characteristics, including its height, spread, and flower colors, making it a valuable resource for gardeners and horticulturists. Original publication date October 1999.